Légifényképek katonai felhasználása . The military applications of aerial photography - írta és rajzolta: Bóné János. (Magyar Diafilmgyártó Vállalat, 1966)
Produced for the staff of the Hungarian National Defence Association Sports Bureau, Reserve Officers' Department. Types of aerial photos, methods of taking them, and their use for mapping. A légi felvételek típusai, készítésük módszerei és térképészeti felhasználásuk.